The farnesoid X receptor modulates renal lipid metabolism and diet-induced renal inflammation, fibrosis, and proteinuria - Wang, Xiaoxin X.; Jiang, Tao; Shen, Yan; Adorini, Luciano; Pruzanski, Mark; Gonzalez, Frank J.; Scherzer, Pnina; Lewis, Linda; Miyazaki-Anzai, Shinobu; Levi, Moshe (American Journal of Physiology - Renal Physiology, 2009)
Diet-induced obesity is associated with proteinuria and glomerular disease in humans and rodents. We have shown that in mice fed a high-fat diet, increased renal expression of the transcriptional factor sterol-regulatory element binding protein-1 (SREBP-1) plays a critical role in renal lipid accumulation and increases the activity of proinflammatory cytokines and profibrotic growth factors. In the current study, we have determined a key role of the farnesoid X receptor (FXR) in modulating renal SREBP-1 activity, glomerular lesions, and proteinuria. We found that feeding a Western-style diet to DBA/2J mice results in proteinuria, podocyte loss, mesangial expansion, renal lipid accumulation, and increased expression of proinflammatory factors, oxidative stress, and profibrotic growth factors. Treatment of these mice with the highly selective and potent FXR-activating ligand 6-α-ethyl-chenodeoxycholic acid (INT-747) ameliorates triglyceride accumulation by modulating fatty acid synthesis and oxidation, improves proteinuria, prevents podocyte loss, mesangial expansion, accumulation of extracellular matrix proteins, and increased expression of profibrotic growth factors and fibrosis markers, and modulates inflammation and oxidative stress. Our results therefore indicate that FXR activation could represent an effective therapy for treatment of abnormal renal lipid metabolism with associated inflammation, oxidative stress, and kidney pathology in patients affected by obesity.